Marasil musannaf Abd al-Razzaq man kitab Al-Zakah - Muhamad Rozaimi Ramle (2014)
The study of al-Maghazi and al-Siyar is considered a practical application of the teachings of the Quran and the Sunnah of the Prophet. Therefore, scholars made efforts to compile the narrations of al-Maghazi and al-Siyar, and to explain. criticize and scrutinize them in order to distinguish the sound (sahih) narrations from the weak (dhaif). Ibn Qayyim al-Jauziyyah is one of the scholars who critically engage with these narrations in his treatise Zaad al-Maad. This research is aimed at elaborating his methodology in the usage of these narrations in argumentation and in the application of al-Isti 'nas (leniency in the usage of al-Maghazi and aiSiyar as supporting evidence ill argument), its conditions, benefits and scopes. TIns study reveals the yardstick which are relied on by Ibn al-Qayyim to criticize the ascription (sanad) and the text (matan) of these narrations in comparison to the yardstick applied by other scholars in textual criticism. This research also focuses on steps taken by Ibn al-Qayyim in dealing with the conflicting narrations in order to derive the principles and methods in removing the contradictions either through the process of harmonization or justified preference. In chapter four, this research deals with the characteristics of Ibn Qayyim's critical thoughts, the factors that influenced him and the impact of his critical thoughts on those people after him in the studies of al-Maghazi and al-Siyar. This research also reveals and explains criticisms towards Ibn aI-Qayyim in his scholarly engagement with the narrations of al-Maghazi and al-Siyar. In this research, I adopt the inductive methodology to extract and elucidate Ibn al-Qayyim's methodology in the usage of ei-Maghazi and al-Siyar in argumentation and in the application a/Isti 'nas whereas the analytical method is used to extract the distinct characteristics of his critical thought. In this research as well, I have used two more methods: the comparative analysis is used to compare Ibn al-Qayyim's critical methodology with other scholars' methodology and critical analysis is used to criticize Ibn al-Qayyim's critical views.